Labelling of 90Y- and 177Lu-DOTA-Bioconjugates for Targeted Radionuclide Therapy: A Comparison among Manual, Semiautomated, and Fully Automated Synthesis. (25th May 2017) - Iori, Michele; Capponi, Pier C.; Rubagotti, Sara; Esposizione, Luca Rosario; Seemann, Johanna; Pitzschler, Riccardo; Dreger, Thorsten; Formisano, Debora; Grassi, Elisa; Fioroni, Federica; Versari, Annibale; Asti, Mattia
Abstract : In spite of the hazard due to the radiation exposure, preparation of 90 Y- and 177 Lu-labelled radiopharmaceuticals is still mainly performed using manual procedures. In the present study the performance of a commercial automatic synthesizer based on disposable cassettes for the labelling of 177 Lu- and 90 Y-DOTA-conjugated biomolecules (namely, DOTATOC and PSMA-617) was evaluated and compared to a manual and a semiautomated approach. The dose exposure of the operators was evaluated as well. More than 300 clinical preparations of both 90 Y- and 177 Lu-labelled radiopharmaceuticals have been performed using the three different methods. The mean radiochemical yields for 90 Y-DOTATOC were 96.2 ± 4.9 %, 90.3 ± 5.6 %, and 82.0 ± 8.4 %, while for 177 Lu-DOTATOC they were 98.3% ± 0.6, 90.8% ± 8.3, and 83.1 ± 5.7 % when manual, semiautomated, and automated approaches were used, respectively. The mean doses on the whole hands for yttrium-90 preparations were 0.15 ± 0.4 mSv/GBq, 0.04 ± 0.1 mSv/GBq, and 0.11 ± 0.3 mSv/GBq for manual, semiautomated, and automated synthesis, respectively, and for lutetium-177 preparations, they were 0.02 ± 0.008 mSv/GBq, 0.01 ± 0.03 mSv/GBq, and 0.01 ± 0.02 mSv/GBq, respectively. In conclusion, the automated approach guaranteed reliable and reproducible preparations of pharmaceutical grade therapeutic radiopharmaceuticals in a decent RCY. The radiation exposure of the operators remained comparable to the manual approach mainly due to the fact that a dedicated shielding was still not available for the system.